PREVENTION AND TREATMENT OF INTRAABDOMINAL HYPERTENSION IN PATIENTS WITH PATHOLOGY OF ABDOMINAL ORGANS - A. Kolosovych (Bogomolets National Medical University, 2016)
Encreased intra-abdominal pressure attracts the attention of scintistslast years. Abdominal compartment syndrome cause the development of acute distress syndrome and multiple organ failure in 40% with a fatal outcome of the disease in 12% of cases. Unfortunately, there is no explicit algorithm of actions to prevent the development of abdominal syndrome in the literature. That's why so importent to search for new technical solutions for the prevention and treatment of intra¬abdominal hypertension in patients with acute surgical pathology of abdominal organs. We analyzed results of treatment of 130 patients with acute surgical diseases of the abdominal cavity, which was accompanied by increased intra-abdominal pressure inthe clinic №2 Department of Surgery National Bogomolets Medical University in the period from 2013 to 2015. Among the acute surgical diseases we have observed the following nosology: strangulated ventral hernia large and giant sizes (11 people), abdominal trauma (36), acute pancreatitis (35), perforated duodenal ulcer (7 people), an acute intestinal obstruction ( 19 people), acute appendicitis (11 persons), acute cholecystitis (11 people). Patients were divided into 2 groups,depending on the selected diagnostic and treatment strategy. The control group included 59 (45.4%) patients who were subject to the standard approaches to diagnostics and treatment. The study group included 71 (54.6%) patients, in which we usedour improved diagnostics and treatment algorithm. The use of improved diagnostics and treatment algorithm for the prevention and treatment of intra¬abdominal hypertension reduced the incidence of systemic complications from 38,98% to 12,7% (p <0,001), local complications - from 25,4% to 9,9% (p < 0.02), all¬cause mortality - from 11.9% to 1,4% (p <0,02), and postoperative mortality - from 11.9% to 0% (p <0,01).